SIMULAKRA MAHASISWA ANTARA MEANINGDAN FUN [Kajian Kritis Pemikiran Jean Baudrillard] - Hariyanto, Ishak Hariyanto; Susilawati, Endang (Universitas Islam Negeri Mataram, 2017)
The presence of students as agent of change, the agent of control, and the moral force is far from what was expected. Because it sees students, especially student UIN Mataram is currently very premature because students just as sheer fun. Such things happened because of the increased media, social sophisticated users are able to make sedated as opium, especially users from among the students as the House of intellect. This article is basically a research writer in the campus environment UIN 2015-2017 Year of Mataram, and data obtained through tracking some of the literature and also interview several students who are actively using social media. The results of this study revealed that the existence of the current students like reading, writing and the apparent discussion no longer untouchable and away from the identity of the Student Center. Because the current students have less awareness in using social media. Lack of awareness due to the sinking of the students with social media that result in a loss of meaning and will survive. Therefore, the current students only as fun. Fun meaning is the role and function of students only as happy-happy alone. The lecture was made in satisfying the wishes of mere means, seeking just satisfaction. Students like him enough with Come, sit down, and Quietly lecture, eventually only as a formality only. Then on the stage that students lose meaning and existence. In addition, students also contracted by simulacra, i.e., their ignorance of the boundary between the real and the artificial, because of the world has now become the world’s imagination, and in infectious simulacra in the body of the student, when a student was helpless again.